Nicotine Enhances Excitability of Medial Habenular Neurons via Facilitation of Neurokinin Signaling - Dao, Dang Q. (Society for Neuroscience, 2014)
The medial habenula (MHb) densely expresses nicotinic acetylcholine receptors (nAChRs) and participates in nicotine-related behaviors such as nicotine withdrawal and regulating nicotine intake. Although specific nAChR subunits are identified as being involved in withdrawal behavior, the cellular mechanisms through which nicotine acts to cause this aversive experience is unclear. Here, we demonstrate an interaction between the nicotinic and neurokinin signaling systems that may form the basis for some symptoms experienced during nicotine withdrawal. Using patch-clamp electrophysiology in mouse brain slices, we show that nicotine (1 μm) increases intrinsic excitability in MHb neurons. This nicotine-induced phenomenon requires α5-containing nAChRs and depends on intact neurokinin signaling. The effect is blocked by preincubation with neurokinin 1 (NK1; L-732138, 10 μm) and NK3 (SB222200, 2 μm) antagonists and mimicked by NK1 (substance P, 100 nm) and NK3 (neurokinin B [NKB], 100 nm) agonists. Microinjections (1 μl) of L-732138 (50 nm) and SB222200 (100 nm) into the MHb induces withdrawal behavior in chronic nicotine-treated (8.4 mg/kg/d, 2 weeks) mice. Conversely, withdrawal behavior is absent with analogous microinjections into the lateral habenula of nicotine-treated mice or in mice chronically treated with a vehicle solution. Further, chronic nicotine reduces nicotine's acute modulation of intrinsic excitability while sparing modulation by NKB. Our work elucidates the interplay between two neuromodulatory signaling systems in the brain through which nicotine acts to influence intrinsic excitability. More importantly, we document a neuroadaptation of this mechanism to chronic nicotine exposure and implicate these mechanisms collectively in the emergence of nicotine withdrawal behavior.